1997
DOI: 10.1002/zaac.19976231030
|View full text |Cite
|
Sign up to set email alerts
|

Mesityloxomolybdän‐ und ‐wolfram‐Verbindungen. I. Die Struktur von LiMoO2Me2Mes(OEt2)2

Abstract: Die Struktur der bekannten, aus MoO2Mes2 1 und LiMe dargestellten Verbindung LiMoO2Me2Mes(OEt2)2 2 [2] sowie ihre NMR‐spektroskopischen Daten werden mitgeteilt. 2 bildet ein in der Raumgruppe P1 kristallisierendes Dimer durch Verknüpfung zweier [MoO2Me2Mes]−‐Anionen über Oxo‐Liganden durch zwei Kationen [Li(OEt2)2]+. Der gebildete [‥OMoOLi‥]2− Achtring ist eben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…It was reported that 1 reacts with MeLi in ether solution under formation of LiOMe and a thermally instable compound with an analytical composition corresponding to the formula Mo(mes) 2 ·(OEt 2 ) 2 2a. Later, the product of the reaction of MeLi and MoO 2 (mes) 2 was found to be of the composition LiMoO 2 Me 2 (mes) 2 (OEt 2 ) 2 ( 2 ). 3a,b The X-ray crystal structure of this compound was determined 3b…”
Section: Synthesis and Reactivitymentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that 1 reacts with MeLi in ether solution under formation of LiOMe and a thermally instable compound with an analytical composition corresponding to the formula Mo(mes) 2 ·(OEt 2 ) 2 2a. Later, the product of the reaction of MeLi and MoO 2 (mes) 2 was found to be of the composition LiMoO 2 Me 2 (mes) 2 (OEt 2 ) 2 ( 2 ). 3a,b The X-ray crystal structure of this compound was determined 3b…”
Section: Synthesis and Reactivitymentioning
confidence: 99%
“…Insertion reactions of 1 with carbon monoxide, 3c,d isocyanides,3e and isocyanates 3f were also studied. 1 reacts with CO in pyridine to give dimesityl ketone and a dihydropyridine dimer, which represented the first example of N-acylation of a pyridine by CO mediated by a transition metal complex 3d.…”
Section: Synthesis and Reactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Auch die Umsetzung von 1 mit Dimesitylmagnesium [12] liefert keine besseren Ergebnisse. Heyn [3] weist darauf hin, daû die Bildung von 2 (und auch von MoOMes 3 [13]) von Nebenreaktionen begleitet wird, und daû bei der Umsetzung von 1 mit Phenylgrignardreagens [3 b] [1]. Trigonal-bipyramidale Strukturen werden ha È ufig fu È r d 0 -Spezies gefunden, wa È hrend d 1 -und d 2 -Zentralatome eher quadratisch-pyramidale Geometrien einnehmen sollen [14].…”
Section: Ergebnisse Und Diskussionunclassified